Measurements of the pressure distribution on swept back wings with trailing edge split flaps: summary of wind tunnel work at the College of Aeronautics 1948 - 50 - Babister, A. W. (College of Aeronautics, Cranfield, 1951)
This is an interim report giving measurement s that have so far been made of pressure distribution on two untapered wings swept back 45◦, aspect ratio 2 and 4, fitted with both full span and part span trailing edge split flaps. The Reynolds number in these tests was about 0.5x106.